Transportation Information: Media Pembelajaran Sistem Transportasi Berbasis Website Untuk Meningkatkan Literasi Mahasiswa - Amalia Azhara; Ilham Kudri; Indah Priyanti Putri Agustiana; Mohammad Surya Fahreza (Jurnal Ilmiah Wahana Pendidikan, 2023)
A world order in which internet/digital media has become the main reference in daily activities. To face the present, of course, we need "new literacy" in addition to old literacy. The purpose of this research is to provide various information to all students about internet/digital literacy which greatly impacts progress in Indonesia. The method used in this study is a qualitative approach, in this study we used literacy sources such as magazines, scientific books, journals, newspapers, and websites (internet) which contain information that is appropriate to the topic being sought. As a student, you are forced not only to understand existing knowledge, such as writing and reading. With this, it is expected that students are highly demanded to have various abilities to process, communicate, collaborate, to create works.